Resident Doctors’ Perspectives and Experiences with Spiritual/Religious Considerations: A Survey-Based Project - Safia Zaffarullah; Tom Robson; Neelima Reddi (BJPsych Open)
Aims: The RCPsych’s position statement recommends a spirituality/religious belief (S/R) history be routinely considered in clinical assessments, and that an understanding of S/R and their relationship to psychiatric disorders are essential components of psychiatric training. In reality, psychiatric training at local and collegiate level is likely lacking in both quality and quantity of training in S/R considerations. There are likely a myriad of factors barring trainees from broaching this topic, which this survey-based QI project sought to explore.